تقييم مبدأ المخاطرة والكسب في المالية الإسلامية وتطبيقه في منتجات التمويل في الصيرفة الإسلامية في ماليزيا Evaluating the Principle of Risk and Reward in Islamic Finance and Its Application to Islamic Banking Financing Products in Malaysia - Hassan, Rusni; Benaicha, Mohamed (International Journal of Al-Turath In Islamic Wealth and Finance, 2021)
يعالج هذا البحث مشكلة غياب دراسة مخصوصة بمبدأ المخاطرة والكسب تتناول جوانبها النظرية والعملية. هناك غياب محاولات إحصاء وتقييم ضوابط مبدأ المخاطرة والكسب – دراسات تمثل لهذه الضوابط تمثيلاً واقعياً في معاملات المصارف الإسلامية المعاصرة. يهدف البحث إلى محاولة تحديد ضوابط مبدأ المخاطرة والكسب، ويهدف كذلك إلى التمثيل لكيفية تنزيل هذه الضوابط على أحدث منتجات التمويل في قطاع الصيرفة الإسلامية في ماليزيا. يعتمد الباحثان منهجاً تحليلياً وصفياً استقرائياً لإحصاء الضوابط النظرية، وتقييمها، وتطبيقها على ممارسات قطاع الصيرفة الإسلامية في ماليزيا من خلال الوثائق المعتمدة والمنشور من قبل صناع السياسات المصرفية، ومن خلال التجربة الريادية لأحد الباحثين في الصناعة. يكشف البحث أن ضوابط مبدأ المخاطرة والكسب هي: أولاً، مخاطر السوق ومخاطر استمرار الملكية ومخاطر الرأسمال وكلها ترجع إلى مصطلح الضمان الفقهي؛ ثانياً، تحمُّل التكاليف التعاقدية المتعلقة بمعاملات التمويل لا ينبغي أن يكون وسيلة لنقل المخاطر؛ ثالثا، يجب أن تحقق معاملات التمويل القيمةَ الاقتصادية المضافة. كذلك يكشف البحث أن المصارف الإسلامية في ماليزيا لا تلتزم بهذه الضوابط إلا شكلياً وبالتالي لا يتجسد مبدأ المخاطرة والكسب بضوابطه الحالية في صناعة المصارفة الإسلامية الماليزية لأسباب ترجع إلى المنطقية، والواقعية، واعتبار المصالح، واعتبار الغرر والربح الفاحشين. أخيراً، يجد البحث أن الضوابط المثالية الثابتة حالياً لا تقوم على نصوص شرعية قوية الصحة، وأن هذه النصوص تم تأويلها تأويلاً سطحياً، الأمر الذي يدعو إلى إعادة تأويل مصادر هذا المبدأ. في نهاية البحث، يقدم الباحثان تأويلات بديلة لهذه النصوص تأخذ في عين الاعتبار عقلانية وواقعية الشريعة. Abstract This study examines the issue of the general lack of dedicated study on the principle of risk and reward in Islamic finance from both a theoretical and a practical perspective. Furthermore, there is an absence of a demonstration of the risk and reward principles in Islamic finance and how their parameters are properly applicable to Islamic finance products and instruments. This study aims to define the aforementioned parameters in Islamic finance and demonstrate how such parameters are applied to Islamic bank financing products in Malaysia. The research applied a qualitative research methodology in inducing the theoretical parameters of risk and reward as well as an analytical approach to evaluating the current parameters based on rationality, practicality and so forth. The study finds the that current parameters of risk and reward are: first, market risks, ownership risk and capital – equity – risk, all of which pertain to dhaman; second, contractual costs should be borne by the appropriate parties and not be a means to transfer risks; finally, financing transactions have to add economic value. Furthermore, the researchers establish that the parameters of risk and reward as they stand are not properly observed by the Malaysian Islamic banking practice for reasons including rationality, practicality, consideration for maslahah, and consideration of excessive risk-to-reward tradeoffs. Finally, the study finds that the current parameters of risk and reward as they stand are not based on solid Shari’ah evidence and more specifically, the texts on which they are based are either not authentic or are subject to different interpretations. The researchers propose an alternative interpretation for such texts and which yield a new set of parameters that consider the rationalism and realistic of the Shari’ah.